A Study of SiR/EPDM Mixtures for Outdoor Insulators - Sykaras, A.; Rajini, V.; Danikas, M.; Sarathi, R. (Engineering, Technology & Applied Science Research, 2017)
This paper deals with the flashover voltages on samples of silicone rubber/ethylene propylene diene monomer (SiR/EPDM) mixtures under the influence of a uniform electric field. Five different mixtures of SiR/EPDM were investigated. Various SiR/EPDM mixtures (100% EPDM, 10% SiR + 90% EPDM, 30% SiR + 70% EPDM, 50% SiR + 50% EPDM, 70% SiR + 30% EPDM, 90% SiR + 10% EPDM, 100% SiR) were tested for different water droplet arrangements, different water conductivities, different droplet volumes as well as different droplet positioning w.r.t. the electrodes. The 50% SiR + 50% EPDM mixture proved to be the best mixture regarding the flashover voltage.